Race and Punishment: Directions for Economic Research - Myers, Samuel L. (American Economic Review, 1984)
The scholarly debate over the nature and cause of the significant racial disparities in prison incarceration rates in the United States has taken on renewed intensity in recent years. Two sorts of activities have spurred the debate. On one hand, researchers such as Alfred Blumstein (1982), Jan Chaiken and Marcia Chaiken (1982), and Joan Petersilia (1983) have begun to use powerful analytic and conceptual tools to scrutinize the hypothesis that racism or racial discrimination exists in the criminal justice system, or that it is the cause of the racial disproportionality of our prisons. On the other hand, minority scholars and public opinion leaders have begun a very visible and vocal attack on the results of the conventional social science community. (See, for example, National Minority Advisory Council on Criminal Justice, 1980.) These activities have stimulated much discussion among public policymakers and legislators. Ranking black members of the U.S. Congress, for example, have gone on record by questioning social science research findings that purport to show that racial discrimination in certain aspects of the criminal justice system does not exist - or, at least, that its alleged existence is not a cause of the greater representation of blacks in the prisons or the criminal population. Economists have not been leaders or even active participants in this debate. This is surprising for several reasons. Many of the conventional tools of econometrics can be called upon to resolve some of the statistical issues in dispute; post-Beckerian models are likely to yield more than negligible benefits in sorting out the theoretical effects of punishment on criminal activities; and radical labor market paradigms may prove useful in examining the historical evolution of prisons and punishment in America. A brief overview of a number of different areas of research on race and punishment will illustrate the inherent potential as well as the unrealized promise of economic approaches.